43.6k views
3 votes
Simplify the expression (4 + 5i)(4 − 5i). 16 − 20i 16 + 20i −9 41

User Loghorn
by
5.3k points

2 Answers

5 votes

Answer:

Cant give as good of as answer like the other person but it is 41!

Explanation:

User Boojum
by
4.1k points
4 votes

Answer:

41

Explanation:

Simplify the following:

(5 i + 4) (-5 i + 4)

Hint: | Multiply 4 + 5 i and 4 - 5 i together using FOIL.

(4 + 5 i) (4 - 5 i) = (4) (4) + (4) (-5 i) + (5 i) (4) + (5 i) (-5 i):

4×4 + 4 (-5 i) + 5 i×4 + 5 i (-5 i)

Hint: | Multiply 4 and 4 together.

4×4 = 16:

16 - 5×4 i + 5 i×4 + 5 i (-5)×i

Hint: | Multiply 4 and -5 together.

4 (-5) = -20:

16 + -20 i + 5 i×4 + 5 i (-5)×i

Hint: | Multiply 5 and 4 together.

5×4 = 20:

16 - 20 i + 20 i + 5 i (-5)×i

Hint: | Combine products of like terms.

5 i (-5)×i = 5 i^2 (-5):

16 - 20 i + 20 i + -5×5 i^2

Hint: | Evaluate i^2.

i^2 = -1:

16 - 20 i + 20 i - 5×5×-1

Hint: | Multiply 5 and -1 together.

5 (-1) = -5:

16 - 20 i + 20 i - 5-5

Hint: | Multiply -5 and -5 together.

-5 (-5) = 25:

16 - 20 i + 20 i + 25

Hint: | Evaluate 16 - 20 i + 20 i + 25.

16 - 20 i + 20 i + 25 = 41:

Answer: 41

User Joey Gough
by
5.2k points